PENGARUH BOKASHI AMPAS TEBU DAN NPK GROWER TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN KEDELAI EDAMAME (Glycine max (L.) Merril) DI MEDIA TANAH GAMBUT - Sri Rahayu Ningsih; Ernita (UIR Press, 2025)
This study aims to determine the effect of the interaction between Agassi Takashi and NPK Grower on the growth and production of edamame soybean plants in peat soil media. This study was conducted at the experimental farm of the Faculty of Agriculture, Riau Islamic University, for 4 months from October 2024 to February 2025. This study used a Completely Randomized Design (CRD) consisting of two factors. The first factor is Agassi Takashi, with 4 levels: 0, 40, 80, and 120 g per plant. The second factor is NPK Grower, with 4 levels: 0, 1, 2, 2.4, and 3.6 g per plant. The parameters observed were plant height, number of effective root nodules, number of primary branches, flowering age, number of fresh pods, and fresh pod weight. The data from this study were analyzed statistically and then subjected to a 5% BNJ test. The results of this study indicate that the interaction between Agassi Takashi and NPK Grower significantly affected plant height, the number of effective root nodules, flowering age, the number of fresh pods, and fresh pod weight. The best treatment was a combination of 120 g Agassi Takashi per plant and 3.6 g NPK Grower per plant. The main effect of Agassi Takashi was significant on all parameters, and the best treatment was 120 g per plant. The main effect of NPK Grower was significant on all parameters, and the best treatment was 3.6 g per plant.